CONCEPTUAL FOUNDATIONS FOR FORMATION OF FAUNISTIC LEGISLATION IN THE CONTEXT OF ECONOMIC, POLITICAL, SOCIAL AND CULTURAL TRANSFORMATIONS UNER GLOBALIZATION - Шеховцов, Володимир Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: doctrinal analysis of formation of faunistic legislation through the prism of economic, political, social and cultural transformation in the context of globalization. Methods: general scientific and special methods of enquiry: dialectical, formal and legal, hermeneutic, structural and functional, comparative methods. Results: there has been conducted the comprehensive review of interdependence of political, economic, social and cultural, ideological evolutionary stage of national development and the formation of new and improvement the current faunistic legislation. It has been found that each of the spheres of social life has significantly different impacts on updating legislation about protection and use of fauna. Discussion: the influence of economic, political, social and ideological factors of national development on the system of faunistic legislation. The formation and evolution of faunistic legislation is determined by the profound political, social, economic and other changes of the spheres of public life. Transformation of economic relations of the state contributed to the establishment of the institute of ownership of the fauna, as well as the obligation of observance the economic measures aimed at the rational use and protection of the fauna by economic entities. The form, state structure and type of state, the configuration of political forces and the state of political relations are recognized as important factors under the influence of which faunistic legislation is developed. Social values alterations in society demonstrate the intensification of the interest of indifferent citizens to ensuring the humane treatment of animals. The radical transformation of economic, political, socio-cultural life of society under the influence of globalization processes causes a dynamic, often chaotic, devoid of prudence and consistency, the development of legislation. Each of these areas of social reality has varying degrees of impact on the development of faunal legislation, but in the aggregate, they contribute to the need to update such legislation, revise existing paradigms and concepts of legal regulation of wildlife protection and use in accordance with leading global trends and the urgency of securing public-private interest the state. Extensive development of the national economy requires the achievement of an optimal model of consonance between the economic ambitions of the state and the priorities of fauna protection.